From speech to writing, from writing to speech: Towards a poetics of orality following five years of research in the Seminario Euraca - Salgado, María (Re-visiones, 2024)
In this article I analyze some compositional strategies of the speech staged by two renowned Spanish films produced towards the end of the Transition period (Navajeros and Deprisa, deprisa). On the basis of a comparative of how both films construct differently the representation of their characters’ speech in the written script and the oral performance of their interpreters upon this script, and attending to the interval opened by the interplay between both instances, I reflect on some ideas of language, writing and orality that in fact collaborate with the production or problematization of stereotyped and passivizing representations of socio-historical subjectivities such as that of youngsters excluded from the economic and cultural “desarrollista” (developmentalist) order to which both films refer; and from here, I ask about a poetics that would tend to propitiate the linguistic agency any subject has as a speaker. This text formalizes as an article some ideas discussed in the framework of Seminario Euraca, a Madrid based collective research on languages and (genealogies of) crisis on going since November 2012.
Keywords: Orality and writing; poetics; Deprisa, deprisa; Navajeros